Consumo e cidadania: práticas cidadãs nas reclamações dos consumidores - Borges, Fábio Mariano (2012)
Modern society has brought a new actor that had not existed: the consumer. Unlike the buyer, the consumer was founded under the principles of bourgeois private property, freedom and equality. The birth of the consumer is recent and its genesis is marked by struggles and demonstrations for various times in history have been blurred with the struggles for rights associated with citizenship. Throughout consumer education, citizenship principles were incorporated into the composition, resulting in consumer rights. More than a new character of modern society, the consumer is also a legal category, with voting power, political role, economic importance and impact on society changes and reconfigurations. And the consumer citizen in fact exist? In this scenario, this paper attempts to investigate how the meeting between the consumer and citizenship in consumer relations, specifically in times of Brazilian consumer complaints. From this then, several other issues are raised: who speaks for the Brazilian consumers? What are the meanings of the existence of a public agency that maintains the consumer instead of demonstrations and collective movements of consumers? You can find echoes in the voices of citizens complaining consumers? To answer these questions, the object of study was limited in complaints filed in person at Procon. The methodology we use systematic observation, following the service of Procon consumer claimants, in-depth interviews with consumers searching for Procon personally care as well as accounts of customers not served by Procon, about how to articulate their rights as citizens in crisis situations in consumption. It was necessary to draw a genealogy of the global consumer and Brazil, forming the basis for understanding the consumer